Achados clínicos, hemodinâmicos e hemogasométricos da infusão contínua de propofol associado ou não ao tramadol em ovelhas submetidas à videolaparoscopia - Lopes, Maristela de Cassia Seúdo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Twenty four sheep, all female, Santa Ines, age ranged from three to six years and mean weight of 41 ± 4 kg, underwent laparoscopy procedures. The ewe were randomly divided in four groups, designated as GP (propofol), GT1,3 (tramadol 1.3), GT2.6 (tramadol 2,6) and GTepi (epidural tramadol). All ewe were induced with propofol (6.0 mg.kg-1 IV) and anesthesia was maintained with a CRI of propofol (0.5 mg.kg.min-1). Analgesia was obtained with tramadol bolus (1.5 mg kg-1) followed by 1.3 mg kg min-1 CRI (GT1.3, n=6); bolus (3.0 mg kg-1) followed by 2.6 mg kg min-1 CRI (GT2.6, n=6) and by infusion of tramadol epidurally (2.0 mg.kg-1). In a control group recieved saline CRI (GP, n=6). The animals underwent mechanical ventilation Hemodynamic, respiratory and metabolic parameters were evaluated during the preoperative (M0) periods, intraoperative (M15 -M30: dorsal recumbence, M30 to M60: with abdomen insufflation and Trendelemburg positioning and M60 - M90: dorsal recumbence without abdomen insufflation). In the same time, we assessed the quality of induction and recovery from anesthesia, plasma cortisol, degree and duration of analgesia (six hours of post surgical) and use of rescue analgesia in the intra and postoperatively. There were no significant changes in heart rate (HR). The body temperature decreased from M30 until the end of anesthesia (M90) in all groups. The partial pressure of oxygen in arterial blood (PaO2) increased in all groups from M15 as well as the partial pressure of carbon dioxide (PaCO2) from the M30 to M60 in GP and GT1.3, from the M50 to M60 in GT2.6 and in M60 in GTepi. There was a decrease in pH from M30 to M70 in GT1.3, from M40 and M90 in GP and GT2.6 and from M40 to M80 in GTepi. In hemodynamic evaluation, cardiac index (CI) decreased from M30 to M60 in animals GP and GTepi and M15 in GT1.3. In stroke volume (SV) was a reduction from M15 to M60 in GP, GT1.3, GT2.6 and from M30 to M70 in GTepi. The rescue analgesia ...

Foram utilizadas 24 ovinos, fêmeas, Santa Inês, com idade entre três a seis anos, com peso médio de 41±4 Kg, submetidas à videolaparoscopia. Os animais foram distribuídos de forma aleatória em quatro grupos, designados como GP (propofol), GT1,3 (tramadol 1,3), GT2,6 (tramadol 2,6) e GTepi (tramadol epidural). Todos os animais foram induzidos e mantidos à anestesia com propofol (6,0 mg/kg/IV) seguido taxa de infusão 0,5 mg/kg/min. A analgesia foi realizada com uso do tramadol administrado na forma de bolus (1,5 mg/kg) seguido pela infusão intravenosa de 1,3 mg/kg/h (GT1,3; n=6); bolus (3,0 mg/kg) seguido pela infusão intravenosa de 2,6 mg/kg/h (GT2,6; n=6) e administrado pela via epidural, na dose de 2,0 mg/kg (GTepi, n=6). Um grupo controle recebeu infusão de solução salina (GP, n=6). Todos os animais foram mantidos em ventilação controlada. Foram avaliados os parâmetros hemodinâmicos, respiratórios e hemogasométricos antes da indução (M0), 15 (M15) e 30 (M30) após o ínicio da infusão de propofol e tramadol ou NaCl0,9%, a cada 10 minutos ( M40, M50 e M60) com o animal em posição de cefalodeclive e com pneumoperitônio e por um período adicional de 30 minutos (M70, M80 e M90) com o animal em decúbito dorsal e sem a presença do pneumoperitônio. Concomitantemente, avaliou-se a qualidade da indução e recuperação anestésica, cortisol plasmático, grau e duração da analgesia (seis horas do pós-cirúrgico) e o uso de analgesia resgate nos períodos intra e pós-operatório. Não houve variações significativas na frequência cardíaca, pressão arterial, pressão de oclusão da artéria pulmonar, índice da resistência vascular sistêmica e índice do trabalho do ventrículo esquerdo. Nos primeiros 15 minutos constatou-se uma diminuição significativa do volume sistólico em todos os grupos, o qual refletiu na redução significativa do índice cardíaco. Durante o pneumoperitônio essa redução se ...
Keywords: Ovino; Analgesia; Opioides; Monitorização hemodinamica; Anestesia intravenosa; Sheep